PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN ASET UUS DENGAN ASET BANK INDUK SEBAGAI VARIABEL INTERVENING DI INDONESIA - Gusniawan, Irvan; Parno, Parno; Mainata, Dedy (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2022)
The background of the research is that UUS's Asset Growth shows good performance. Therefore, a more in-depth observation and analysis is needed to observe the growth of UUS's assets. The research objectives are to examine the effect of NPF, NOM, and BOPO on UUS asset growth, and to examine the effect of NPF, NOM, and BOPO on parent assets, as well as to examine the effect of NPF, NOM, and BOPO on UUS asset growth mediated by parent assets. The research method in this study is quantitative research using secondary data types in the form of monthly reports that have been published by the OJK and each Parent Bank that has UUS through its official website, which consists of 20 samples of Islamic Business Units. The dependent variable used is UUS Asset Growth, the independent variable is the financial performance of NPF, NOM, and BOPO, and the Intervening Variable is the assets of the parent bank. The analytical method used in this study is Mediation Variable Regression with the help of IBM SPSS Statistics 22 software. The results of this study indicate that partially NPF has a significant negative effect on UUS Asset Growth, namely the lower the NPF ratio, the better. The NOM has a significant negative effect on UUS Asset Growth, indicating that the ratio is not good, meaning that the profits obtained are still relatively small. Likewise, BOPO has a negative effect on UUS Asset Growth, the lower the ratio, the better. Meanwhile, parent bank assets have a positive effect on UUS asset growth. And simultaneously NPF, NOM, BOPO, and the assets of the parent bank have a positive effect on the growth of UUS assets. Partially, NPF also has a negative effect on the parent bank's assets, meaning that the NPF on the parent bank's assets is quite good. The NOM has a negative effect on the Parent Bank's assets, meaning that the ratio is not good because the lower the profit, the less profit. While the BOPO has a negative effect on the Parent Bank's assets, this indicates that the ratio is quite good. And NPF has a negative effect on UUS Asset Growth mediated by its Parent Assets. Meanwhile, NOM has a negative effect on UUS Asset Growth mediated by its Parent Assets. Likewise, BOPO has a negative effect on UUS Asset Growth mediated by its Parent Assets period 2015-2020.